Tumour necrosis factor receptor superfamily member 9 (TNFRSF9) is up‐regulated in reactive astrocytes in human gliomas. (February 2015) - Blank, Anna‐Eva; Baumgarten, Peter; Zeiner, Pia; Zachskorn, Cornelia; Löffler, Christian; Schittenhelm, Jens; Czupalla, Cathrin J.; Capper, David; Plate, Karl H.; Harter, Patrick N.; Mittelbronn, Michel
Abstract : Aims: The prognosis of patients with malignant gliomas is still dismal despite maximum treatment. Novel therapeutic alternatives targeting tumorigenic pathways are, therefore, demanded. In murine glioma models, targeting of tumour necrosis factor receptor superfamily (TNFRSF) 9 led to complete tumour eradication. Thus, TNFRSF9 might also constitute a promising target in human diffuse gliomas. As there is a lack of data, we aimed to define the expression pattern and cellular source of TNFRSF9 in human gliomas. Methods: We investigated TNFRSF9 expression in normal human central nervous system (CNS) tissue and glioma specimens using immunohistochemistry, immunofluorescence and Western blotting techniques. Results: Our results show that TNFRSF9 is considerably up‐regulated in human gliomas when compared with normal brain tissue. In addition, our data provides evidence for an immune cell‐independent de novo expression pattern of TNFRSF9 in mainly non‐neoplastic reactive astrocytes and excludes classic immunological cell types, namely lymphocytes and microglia as the source of TNFRSF9. Moreover, TNFRSF9 is predominantly expressed in a perivascular and peritumoural distribution with significantly higher expression in IDH‐1 mutant gliomas. Conclusions: Our findings provide a novel, TNFRSF9‐positive, reactive astrocytic phenotype and challenge the therapeutic suitability of TNFRSF9 as a promising target for human gliomas.